Implementasi strategi public relation sebagai media promosi produk perbankan - Fitrihcahya, Rahmadani Aidil (Maliki Interdisciplinary Journal, 2026)
Banking as a financial institution that functions as a center for allocating funds in the economy, requires an effective communication strategy to increase brand awareness, motivate purchases and maintain customer loyalty. This article discusses the relationship between public relations (PR) in promotional media for banking products, with a focus on the implications of communication strategies and optimal media choices. Print media, such as brochures, newspapers, and magazines, remains relevant in some situations. However, its effectiveness is often influenced by reader preferences and level of exposure. Electronic media, radio, and television, are popular platforms for banking product promotion. Public relations plays a central role in banking product promotion. With a combination of effective communication strategies, appropriate media choices, and integrated implementation, banks can increase brand awareness, motivate purchases, and maintain customer loyalty.